COMPLEX TECHNOLOGICAL AND BIOLOGICAL RESEARCH OF SOLUTIONS FOR PERITONEAL DIALYSIS - Hudz, Nataliia; Korytniuk, Raisa; Vyshnevska, Liliia; Wieczorek, Piotr P. (International Journal of Applied Pharmaceutics, 2018)
Objective: The purpose of our work was to conduct technological, analytical, and biological investigations and stability studies of peritoneal dialysis (PD) solutions containing glucose and sodium lactate in single-chamber containers. Methods: Different formulations of PD solutions were prepared and sterilized at a temperature of 121 Â°C during 15 m. UV-spectrophotometric determination was performed using purified water as a blank. The spectra of the solutions were run in the range of 220 to 400 nm for the identification of an absorption maximum (Î»max) and measuring the absorbance at 228-230 nm and Î»maxbefore and after heat sterilization. Î»max of the most PD solutions after sterilization was found in the range of 273 to 281 nm. The potentiometric determination was done for pH measuring PD solutions before and after sterilization. Alternative analytical procedure of direct argent metric method was employed for fast measuring content of chloride ions. Viability of Vero cells was evaluated using 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) test, neutral red (NR) uptake assay, and sulforhodamine B (SRB) test. Results: The results showed that the absorbance of the most laboratory batches of PD solutions augments significantly with increasing an autoclave heating time to the sterilization temperature and time of its cooling after sterilization. The longer these parameters, the higher is the absorbance at 228-230 and 273-281 nm indicating 3,4-dideoxyglucoson-3-en (3,4-DGE) and 5-hydroxymethylfurfural (5-HMF) contents, respectively. Glucose degradation is practically absent at short terms of heating and cooling an autoclave while sterilized samples are preserved sterile. Stability studies showed a significant decrease in the absorbance at 228-230 nm during storage with the achievement of a nadir and the following weak increase; an elevation or decrease in the absorption maximum; a substantial decline in the pH of the solution after sterilization and an insignificant pH decrease during storage. The viability of kidney cells was the highest in the SRB test and the lowest one was in the MTT test. Conclusion: The influence of sterilization regimes on the quality of conventional PD solutions and their stability during storage were studied. The highest cytotoxicity was detected in the MTT test, and the lowest one was done in the SRB test, indicating the largest vulnerability of mitochondria under the influence of PD solutions compared to the membranes permeability, functioning of kidney cell lysosomes and the ability of cells to synthesize proteins. Our studies could be useful in the context of planning development of PD solutions with the purpose of authorization and domestic manufacture of these solutions in low-and-middle-income countries.